2013
DOI: 10.1111/jvs.12079
|View full text |Cite
|
Sign up to set email alerts
|

Inferring shifts in tree species distribution using asymmetric distribution curves: a case study in the Iberian mountains

Abstract: Questions The objectives of this study were to examine altitudinal shifts in tree species distributions over one decade to quantify the potential for tree migration. Location Spain. Methods We analysed presence–absence data using two successive surveys of the Spanish Forest Inventory in five Fagaceae tree species (two temperate: Fagus sylvatica and Quercus petraea, one sub‐Mediterranean: Q. faginea and two Mediterranean: Q. suber and Q. ilex) in two mountain ranges (the Pyrenees and the Iberian system). Half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 66 publications
1
37
1
3
Order By: Relevance
“…According to the RF results, elevation was introduced as the most important factor in the process of modelling. Our results corroborated previous studies [22,26,36,80,81] when we tried to examine the relationship between elevation and the spatial occurrence of species. However, our results contradicted the results of Wheatley et al [32].…”
Section: Topographic Variablessupporting
confidence: 82%
“…According to the RF results, elevation was introduced as the most important factor in the process of modelling. Our results corroborated previous studies [22,26,36,80,81] when we tried to examine the relationship between elevation and the spatial occurrence of species. However, our results contradicted the results of Wheatley et al [32].…”
Section: Topographic Variablessupporting
confidence: 82%
“…Some will be too conservative because of overlooked individuals or exclusion of individuals with nonverified identifications. Contrary to Sklenár's claim (1), the rates reported are within previous observations (6)(7)(8). Furthermore, Sklenár uses post-Humboldt collections to compare shifts, but most were collected by Meyer and Whymper on the northwestern and western slopes (3,9), and hence are incomparable to our study.…”
contrasting
confidence: 55%
“…An increasing body of empirical studies has shown that tree species populations located at their colder limits moved poleward or upward due to global changes (e.g., Walther et al 2005;Penuelas et al 2007; Batllori and Gutierrez 2008;Beckage et al 2008;Devi et al 2008;Parolo and Rossi 2008;Zhu et al 2012;Delzon et al 2013). On the contrary, evidences of extirpation events at their warmer edges remain rare (Allen and Breshears 1998;Penuelas and Boada 2003;Beckage et al 2008;Zhu et al 2012;Urli et al 2014). The difference in detecting colonization and extirpation events of populations located at each edge are explained by the apparent higher stability of local populations at their warmer limit compared to those located at the colder edge.…”
Section: Introductionmentioning
confidence: 71%